Acute Symptomatic Epileptic Seizures After Microsurgical Removal of Supratentorial Meningiomas - D. I. Abzalova; A. V. Prirodov; M. V. Sinkin; P. I. Solovyeva; I. I. Goncharova (Неотложная медицинская помощь, 2024)
RELEVANCE. One of the problems complicating the early postoperative period in patients with supratentorial meningiomas is epileptic seizures, which in 9-16% of cases first develop within the first 7 days after tumor removal (acute symptomatic epileptic seizures).AIM OF THE STUDY. To identify risk factors for the occurrence of acute symptomatic epileptic seizures in the early postoperative period in patients with supratentorial meningiomas and to evaluate the effectiveness of prophylactic antiepileptic therapy.MATERIAL AND METHODS. A prospective, single-blind, randomized, placebo-controlled study was conducted using the sequential, alternate-arm randomization method. The treatment of 102 patients with supratentorial meningiomas was analyzed, in whom the tumor was removed between 01.01.2021 and 30.09.2023 at the N.V. Sklifosovsky Research Institute for Emergency Medicine. To identify risk factors for the development of acute symptomatic epileptic seizures in patients, we assessed the data of the anamnesis, examination of the patient, electroencephalography before surgery, neuroimaging before and after tumor resection, as well as the characteristics of the intraoperative period, duration and outcomes of hospitalization. To evaluate the effectiveness of the prophylactic use of antiepileptic drugs, patients were divided into two groups. The first group consisted of 49 patients who took an antiepileptic drug as a prophylaxis of early epileptic seizures. The second group consisted of 53 patients who took a placebo drug. Both groups were divided into two subgroups each depending on the development of an epileptic seizure or its absence after surgery. In the first group, patients with epileptic seizures were considered the main subgroup, the patients without seizures were considered the control. We assessed the placebo group similarly.RESULTS. In the placebo group, a risk factor for the development of acute symptomatic epileptic seizures was the transection of one or more veins, which was necessary to achieve sufficient surgical access, leading to a change in cerebral venous blood flow (p=0.013, odds ratio (OR)=11.43; 95% CI [1.75–74.73]). In both the antiepileptic drug group and the placebo group, risk factors included an increase in the volume of cerebral edema according to postoperative CT scan data compared with preoperative (p=0.05, OR=18.8; 95% CI [2.0–182.7] and p=0.01, OR=12.6; 95% CI [2.36–68.0], respectively), as well as hemorrhagic transformation of the perifocal edema zone (p=0.03, OR=8.75; 95% CI [1.36–56.4] and p=0.02, OR=9.7; 95% CI [2.1–44.6], respectively). The efficacy of prophylactic use of antiepileptic drugs in reducing the incidence of acute symptomatic epileptic seizures in the first 7 days after surgery was not established (p=0.295, OR=0.533; 95% CI [0.181–1.572]).CONCLUSION. We have identified the following risk factors for the development of acute symptomatic epileptic seizures: an increase in the volume of cerebral edema compared to the preoperative level according to postoperative computed tomography, the development of hemorrhagic transformation of cerebral edema in both groups, and the intersection of one or more veins during surgery (in the placebo group). Confirmation of the efficacy of routine use of antiepileptic drugs for the prevention of acute symptomatic epileptic seizures not received.